Method for improving tensile strength of metal connecting piece material

By using raw materials such as titanium powder and aluminum powder, combined with mixing, blanking, laser ignition, vacuum induction smelting and ultrasonic treatment, metal connector materials are prepared, which solves the internal stress problems and tissue unevenness caused by heat treatment in the prior art, and significantly improves the tensile strength and vibration fatigue resistance of the material.

CN119530683AInactive Publication Date: 2025-02-28NINGBO COFAR HOSE & FITTINGS
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510073437.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing metal connectors are prone to internal stress during heat treatment, resulting in defects such as material cracks and deformation, and it is difficult to ensure the uniformity of tissue in complex shapes in heat treatment, resulting in inconsistent strength.

Method used

Titanium powder, aluminum powder, niobium powder, chromium powder, cobalt powder, high-entropy alloy powder and reinforced fibers are used as raw materials to prepare metal connecting parts materials through mixing, blanking, laser ignition, vacuum induction smelting and ultrasonic treatment.

Benefits of technology

It effectively improves the tensile strength and vibration fatigue resistance of metal connector materials, ensuring the quality and quality of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of metal material production, in particular to a method for improving the tensile strength of a metal connecting piece material. The method comprises the steps that titanium powder, aluminum powder, niobium powder, chromium powder, cobalt powder, high-entropy alloy powder and reinforced fibers are put into mixing equipment to be mixed, after uniform mixing, the obtained mixed material is subjected to blank pressing treatment to obtain a blank, the obtained blank is subjected to laser ignition in the argon atmosphere to obtain an alloy blank, then the obtained alloy blank is subjected to vacuum induction melting, and the alloy is obtained. And an ultrasonic probe is inserted into the alloy liquid for ultrasonic treatment, then the alloy liquid is poured, and after cooling, a finished product of the metal connecting piece material is obtained. According to the method for improving the tensile strength of the metal connecting piece material, the mechanical property of the prepared metal connecting piece material can be effectively improved, and the vibration fatigue resistance can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal material production, and in particular to a method for improving the tensile strength of a metal connector material. Background Art

[0002] Metal connectors play a vital role in many industrial fields, such as aerospace, automobile manufacturing, mechanical engineering, electronic equipment and energy industries. They are responsible for firmly connecting various components together to ensure the integrity and reliability of the entire structure when subjected to complex external forces. For example, in automobile manufacturing, the connectors of the engine, chassis and various parts of the body must be able to withstand frequent vibrations, impacts, and tensile and torsion forces under different road conditions to ensure the normal driving and service life of the car.

[0003] Heat treatment is one of the commonly used methods to improve the strength of metals, such as quenching, tempering, and normalizing. However, the quenching process easily leads to large internal stress in the material. If the subsequent treatment such as tempering is not done properly, the material may have defects such as cracks and deformation, affecting its performance and yield rate. Moreover, for some connectors with complex shapes, it is difficult to ensure the uniformity of the structure of each part during heat treatment, resulting in inconsistency in overall strength.

[0004] Based on this, the present invention provides a method for improving the tensile strength of metal connector materials to solve the above-mentioned technical problems. Summary of the invention

[0005] The purpose of the present invention is to provide a method for improving the tensile strength of metal connector materials. The provided method for improving the tensile strength of metal connector materials can not only effectively improve the mechanical properties of the prepared metal connector materials, but also improve the vibration fatigue resistance.

[0006] To achieve the above object, the present invention provides the following technical solutions: The present invention provides a method for improving the tensile strength of a metal connector material, wherein the metal connector material is composed of the following raw materials in parts by weight: 8 to 12 parts of titanium powder, 10 to 15 parts of aluminum powder, 5 to 10 parts of niobium powder, 5 to 8 parts of chromium powder, 4 to 7 parts of cobalt powder, 6 to 10 parts of high entropy alloy powder and 4 to 8 parts of reinforcing fiber; The method for improving the tensile strength of the metal connecting piece material comprises the following steps: Step 1: Accurately weigh titanium powder, aluminum powder, niobium powder, chromium powder, cobalt powder, high entropy alloy powder and reinforcing fiber, and put the titanium powder, aluminum powder, niobium powder, chromium powder, cobalt powder, high entropy alloy powder and reinforcing fiber into a mixing equipment for mixing; Step 2: After the mixture is evenly mixed, the mixture is pressed into a green compact to obtain a green compact; Step 3, igniting the obtained billet by laser in an argon atmosphere to obtain an alloy billet; Step 4: subjecting the obtained alloy billet to vacuum induction melting, and inserting an ultrasonic probe into the alloy liquid for ultrasonic treatment; Step 5: Then pour the alloy liquid, and after cooling, obtain the finished metal connector material.

[0007] The present invention is further configured as follows: the preparation process of the high entropy alloy powder is as follows: Accurately weigh iron powder, nickel powder, manganese powder, tantalum powder and yttrium powder and set aside; The iron powder, nickel powder, manganese powder, tantalum powder and yttrium powder are placed in a planetary ball mill, stearic acid is added thereto, and ball milling is performed under an argon atmosphere to obtain a high entropy alloy powder; The added amount mass ratio of the iron powder, nickel powder, manganese powder, tantalum powder and yttrium powder is 1:1.05-1.12:1.14-1.25:0.85-0.95:0.68-0.82; The added amount of the stearic acid is 0.2-0.3% of the total mass of the iron powder, nickel powder, manganese powder, tantalum powder and yttrium powder.

[0008] The present invention is further configured as follows: the ball-to-material ratio of the ball mill is 7.2-7.5:1, the rotation speed of the ball mill is 150-160 r / min, and the ball milling time is 100-120 min.

[0009] The present invention is further configured as follows: the preparation process of the reinforcing fiber is as follows: The composite material is placed in ethanol at a mass ratio of 0.2 to 0.3:1, heated to 40 to 50°C at 200 to 400 r / min, and then stirred for 60 to 100 minutes to obtain a pre-formulated solution; The boron fiber is completely immersed in the pre-prepared solution for 20 to 30 minutes, taken out, and naturally dried at room temperature, and then the immersed state is repeated 3 to 4 times, and then the dried boron fiber is placed in a tubular furnace, and the temperature is increased to 850 to 950°C at a heating rate of 5 to 10°C / min under a nitrogen atmosphere, and the temperature is kept for 90 to 120 minutes; After completion, the reaction mixture was cooled to room temperature at a cooling rate of 3 to 8°C / min under a nitrogen atmosphere to obtain reinforced fibers.

[0010] The present invention is further configured as follows: the composite material is compounded by phenolic resin and furfural in a mass ratio of 1:2.2-2.5.

[0011] The present invention is further configured as follows: the pressure applied in the green compaction process is 120-130 kN, and the holding time is 10-15 s.

[0012] The present invention is further configured as follows: the laser power used for the laser ignition is 1500-1800W, the spot diameter is 18-22mm, and the irradiation time is 12-20s.

[0013] The present invention is further configured as follows: the process of vacuum induction melting is as follows: The first stage: power is 20KW, time is 10-12 minutes; The second stage: power is 40KW, time is 10-12 minutes; The third stage: the power is 80KW, until the alloy is completely melted; The fourth stage: the power is 100KW and the time is 20 to 30 minutes.

[0014] The present invention is further configured as follows: the vacuum degree of the vacuum induction melting is less than 2Pa.

[0015] The present invention is further configured as follows: the power of the ultrasonic treatment is 1200-1500W, the ultrasonic frequency is 20-22KHz, and the time is 4-6s.

[0016] Compared with the prior art, the present invention has the following beneficial effects: In the present invention, titanium powder, aluminum powder, niobium powder, chromium powder, cobalt powder, high entropy alloy powder and reinforcing fiber are used as raw materials. Titanium powder, aluminum powder, niobium powder, chromium powder, cobalt powder, high entropy alloy powder and reinforcing fiber are put into a mixing device for mixing. After being evenly mixed, the obtained mixed material is pressed into a blank to obtain a blank. The obtained blank is laser ignited under an argon atmosphere to obtain an alloy blank. The obtained alloy blank is then vacuum induction melted, an ultrasonic probe is inserted into the alloy liquid for ultrasonic treatment, and then the alloy liquid is poured. After cooling, a finished metal connector material is obtained. The method for improving the tensile strength of the metal connector material provided by the present invention can not only effectively improve the mechanical properties of the prepared metal connector material, but also improve the anti-vibration fatigue performance, and effectively ensure its quality. The method for improving the tensile strength of the metal connector material provided by the present invention has a broader market prospect and is more suitable for promotion. DETAILED DESCRIPTION

[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1

[0018] The present embodiment provides a method for improving the tensile strength of a metal connector material, wherein the metal connector material is composed of the following raw materials in parts by weight: 8 parts of titanium powder, 10 parts of aluminum powder, 5 parts of niobium powder, 5 parts of chromium powder, 4 parts of cobalt powder, 6 parts of high entropy alloy powder and 4 parts of reinforcing fiber.

[0019] Among them, the preparation process of high entropy alloy powder is as follows: Accurately weigh iron powder, nickel powder, manganese powder, tantalum powder and yttrium powder and set aside; The iron powder, nickel powder, manganese powder, tantalum powder and yttrium powder are placed in a planetary ball mill, stearic acid is added thereto, and ball milling is performed under an argon atmosphere to obtain a high entropy alloy powder; Furthermore, the added amount mass ratio of iron powder, nickel powder, manganese powder, tantalum powder and yttrium powder is 1:1.05:1.14:0.85:0.68; The added amount of stearic acid is 0.2% of the total mass of iron powder, nickel powder, manganese powder, tantalum powder and yttrium powder.

[0020] In addition, the ball-to-material ratio of the ball mill is 7.2:1, the rotation speed of the ball mill is 150 r / min, and the ball milling time is 100 min.

[0021] The preparation process of the reinforcing fiber is as follows: The composite material was placed in ethanol at a mass ratio of 0.2:1, heated to 40°C at 200 r / min, and then stirred for 60 min to obtain a pre-prepared solution; The boron fiber was completely immersed in the pre-prepared solution for 20 minutes, taken out, and naturally dried at room temperature, and then immersed for 3 times. Then, the dried boron fiber was placed in a tubular furnace, and heated to 850°C at a heating rate of 5°C / min under a nitrogen atmosphere, and kept warm for 90 minutes; After completion, the reaction mixture was cooled to room temperature at a cooling rate of 3°C / min under a nitrogen atmosphere to obtain reinforced fibers.

[0022] Furthermore, the composite material is compounded by phenolic resin and furfural in a mass ratio of 1:2.2.

[0023] In this embodiment, it should be noted that the phenolic resin was purchased from Jinan Dahui Chemical Technology Co., Ltd., the furfural was purchased from Shandong Qiyun Chemical Technology Co., Ltd., and the boron fiber was purchased from Hubei Langbowan Biomedicine Co., Ltd.

[0024] In addition, the method for improving the tensile strength of the metal connector material provided in this embodiment includes the following steps: Step 1: Accurately weigh titanium powder, aluminum powder, niobium powder, chromium powder, cobalt powder, high entropy alloy powder and reinforcing fiber, and put the titanium powder, aluminum powder, niobium powder, chromium powder, cobalt powder, high entropy alloy powder and reinforcing fiber into a mixing equipment for mixing.

[0025] Step 2: After the mixture is evenly mixed, the mixture is pressed into a green compact to obtain a green compact.

[0026] The pressure applied in the compacting process is 120 kN, and the holding time is 10 s.

[0027] Step 3: ignite the obtained billet by laser in an argon atmosphere to obtain an alloy billet.

[0028] Among them, the laser power used for laser ignition is 1500W, the spot diameter is 18mm, and the irradiation time is 12s.

[0029] Step 4: subjecting the obtained alloy billet to vacuum induction melting, and inserting an ultrasonic probe into the alloy liquid for ultrasonic treatment.

[0030] Among them, the process of vacuum induction melting is as follows: The first stage: power is 20KW, time is 10min; The second stage: power is 40KW, time is 10min; The third stage: the power is 80KW, until the alloy is completely melted; The fourth stage: power is 100KW, time is 20min; The vacuum degree of vacuum induction melting is 1Pa.

[0031] The power of ultrasonic treatment was 1200 W, the frequency of ultrasonic treatment was 20 KHz, and the time was 4 s.

[0032] Step 5: Then pour the alloy liquid, and after cooling, obtain the finished metal connector material. Example 2

[0033] The present embodiment provides a method for improving the tensile strength of a metal connector material, wherein the metal connector material is composed of the following raw materials in parts by weight: 9 parts of titanium powder, 11 parts of aluminum powder, 6 parts of niobium powder, 6 parts of chromium powder, 5 parts of cobalt powder, 7 parts of high entropy alloy powder and 5 parts of reinforcing fiber.

[0034] Among them, the preparation process of high entropy alloy powder is as follows: Accurately weigh iron powder, nickel powder, manganese powder, tantalum powder and yttrium powder and set aside; The iron powder, nickel powder, manganese powder, tantalum powder and yttrium powder are placed in a planetary ball mill, stearic acid is added thereto, and ball milling is performed under an argon atmosphere to obtain a high entropy alloy powder; Furthermore, the added amount mass ratio of iron powder, nickel powder, manganese powder, tantalum powder and yttrium powder is 1:1.06:1.16:0.87:0.7; The added amount of stearic acid is 0.3% of the total mass of iron powder, nickel powder, manganese powder, tantalum powder and yttrium powder.

[0035] In addition, the ball-to-material ratio of the ball mill is 7.3:1, the rotation speed of the ball mill is 152 r / min, and the ball milling time is 105 min.

[0036] The preparation process of the reinforcing fiber is as follows: The composite material was placed in ethanol at a mass ratio of 0.3:1, heated to 42°C at 210 r / min, and then stirred for 70 min to obtain a pre-formulated solution; The boron fiber was completely immersed in the pre-prepared solution for 22 minutes, taken out, and naturally dried at room temperature, and then immersed for 3 times. Then, the dried boron fiber was placed in a tubular furnace, and heated to 860°C at a heating rate of 6°C / min under a nitrogen atmosphere, and kept warm for 96 minutes; After completion, the reaction mixture was cooled to room temperature at a cooling rate of 4°C / min under a nitrogen atmosphere to obtain reinforced fibers.

[0037] Furthermore, the composite material is compounded by phenolic resin and furfural in a mass ratio of 1:2.3.

[0038] In this embodiment, it should be noted that the phenolic resin was purchased from Jinan Dahui Chemical Technology Co., Ltd., the furfural was purchased from Shandong Qiyun Chemical Technology Co., Ltd., and the boron fiber was purchased from Hubei Langbowan Biomedicine Co., Ltd.

[0039] In addition, the method for improving the tensile strength of the metal connector material provided in this embodiment includes the following steps: Step 1: Accurately weigh titanium powder, aluminum powder, niobium powder, chromium powder, cobalt powder, high entropy alloy powder and reinforcing fiber, and put the titanium powder, aluminum powder, niobium powder, chromium powder, cobalt powder, high entropy alloy powder and reinforcing fiber into a mixing equipment for mixing.

[0040] Step 2: After the mixture is evenly mixed, the mixture is pressed into a green compact to obtain a green compact.

[0041] The pressure applied in the compacting process is 122 kN, and the holding time is 11 s.

[0042] Step 3: ignite the obtained billet by laser in an argon atmosphere to obtain an alloy billet.

[0043] Among them, the laser power used for laser ignition is 1600W, the spot diameter is 19mm, and the irradiation time is 13s.

[0044] Step 4: subjecting the obtained alloy billet to vacuum induction melting, and inserting an ultrasonic probe into the alloy liquid for ultrasonic treatment.

[0045] Among them, the process of vacuum induction melting is as follows: The first stage: power is 20KW, time is 11 minutes; The second stage: power is 40KW, time is 11 minutes; The third stage: the power is 80KW, until the alloy is completely melted; Stage 4: Power is 100KW, time is 22min; The vacuum degree of vacuum induction melting is 1.2Pa.

[0046] The power of ultrasonic treatment was 1300 W, the frequency of ultrasonic treatment was 21 KHz, and the time was 5 s.

[0047] Step 5: Then pour the alloy liquid, and after cooling, obtain the finished metal connector material. Example 3

[0048] The present embodiment provides a method for improving the tensile strength of a metal connector material, wherein the metal connector material is composed of the following raw materials in parts by weight: 10 parts of titanium powder, 12 parts of aluminum powder, 7 parts of niobium powder, 6 parts of chromium powder, 5 parts of cobalt powder, 8 parts of high entropy alloy powder and 6 parts of reinforcing fiber.

[0049] Among them, the preparation process of high entropy alloy powder is as follows: Accurately weigh iron powder, nickel powder, manganese powder, tantalum powder and yttrium powder and set aside; The iron powder, nickel powder, manganese powder, tantalum powder and yttrium powder are placed in a planetary ball mill, stearic acid is added thereto, and ball milling is performed under an argon atmosphere to obtain a high entropy alloy powder; Furthermore, the added amount mass ratio of iron powder, nickel powder, manganese powder, tantalum powder and yttrium powder is 1:1.1:1.19:0.9:0.75; The added amount of stearic acid is 0.3% of the total mass of iron powder, nickel powder, manganese powder, tantalum powder and yttrium powder.

[0050] In addition, the ball-to-material ratio of the ball mill is 7.3:1, the rotation speed of the ball mill is 155 r / min, and the ball milling time is 110 min.

[0051] The preparation process of the reinforcing fiber is as follows: The composite material was placed in ethanol at a mass ratio of 0.3:1, heated to 45°C at 300 r / min, and then stirred for 80 min to obtain a pre-prepared solution; The boron fiber was completely immersed in the pre-prepared solution for 25 minutes, taken out, and naturally dried at room temperature, and then immersed for 4 times. Then, the dried boron fiber was placed in a tubular furnace, and heated to 900°C at a heating rate of 7°C / min in a nitrogen atmosphere, and kept warm for 105 minutes. After completion, the reaction mixture was cooled to room temperature at a cooling rate of 5°C / min under a nitrogen atmosphere to obtain reinforced fibers.

[0052] Furthermore, the composite material is compounded by phenolic resin and furfural in a mass ratio of 1:2.3.

[0053] In this embodiment, it should be noted that the phenolic resin was purchased from Jinan Dahui Chemical Technology Co., Ltd., the furfural was purchased from Shandong Qiyun Chemical Technology Co., Ltd., and the boron fiber was purchased from Hubei Langbowan Biomedicine Co., Ltd.

[0054] In addition, the method for improving the tensile strength of the metal connector material provided in this embodiment includes the following steps: Step 1: Accurately weigh titanium powder, aluminum powder, niobium powder, chromium powder, cobalt powder, high entropy alloy powder and reinforcing fiber, and put the titanium powder, aluminum powder, niobium powder, chromium powder, cobalt powder, high entropy alloy powder and reinforcing fiber into a mixing equipment for mixing.

[0055] Step 2: After the mixture is evenly mixed, the mixture is pressed into a green compact to obtain a green compact.

[0056] The pressure applied in the compacting process is 125 kN, and the holding time is 12 s.

[0057] Step 3: ignite the obtained billet by laser in an argon atmosphere to obtain an alloy billet.

[0058] Among them, the laser power used for laser ignition is 1650W, the spot diameter is 20mm, and the irradiation time is 16s.

[0059] Step 4: subjecting the obtained alloy billet to vacuum induction melting, and inserting an ultrasonic probe into the alloy liquid for ultrasonic treatment.

[0060] Among them, the process of vacuum induction melting is as follows: The first stage: power is 20KW, time is 11 minutes; The second stage: power is 40KW, time is 11 minutes; The third stage: the power is 80KW, until the alloy is completely melted; The fourth stage: power is 100KW, time is 25min; The vacuum degree of vacuum induction melting is 1.5Pa.

[0061] The power of ultrasonic treatment was 1350 W, the frequency of ultrasonic treatment was 21 KHz, and the time was 5 s.

[0062] Step 5: Then pour the alloy liquid, and after cooling, obtain the finished metal connector material. Example 4

[0063] The present embodiment provides a method for improving the tensile strength of a metal connector material, wherein the metal connector material is composed of the following raw materials in parts by weight: 11 parts of titanium powder, 14 parts of aluminum powder, 9 parts of niobium powder, 7 parts of chromium powder, 6 parts of cobalt powder, 9 parts of high entropy alloy powder and 7 parts of reinforcing fiber.

[0064] Among them, the preparation process of high entropy alloy powder is as follows: Accurately weigh iron powder, nickel powder, manganese powder, tantalum powder and yttrium powder and set aside; The iron powder, nickel powder, manganese powder, tantalum powder and yttrium powder are placed in a planetary ball mill, stearic acid is added thereto, and ball milling is performed under an argon atmosphere to obtain a high entropy alloy powder; Furthermore, the added amount mass ratio of iron powder, nickel powder, manganese powder, tantalum powder and yttrium powder is 1:1.11:1.22:0.92:0.8; The added amount of stearic acid is 0.3% of the total mass of iron powder, nickel powder, manganese powder, tantalum powder and yttrium powder.

[0065] In addition, the ball-to-material ratio of the ball mill is 7.4:1, the rotation speed of the ball mill is 158 r / min, and the ball milling time is 115 min.

[0066] The preparation process of the reinforcing fiber is as follows: The composite material was placed in ethanol at a mass ratio of 0.3:1, heated to 48°C at 350 r / min, and then stirred for 90 min to obtain a pre-prepared solution; The boron fiber was completely immersed in the pre-prepared solution for 28 minutes, taken out, and naturally dried at room temperature, and then the immersed solution was repeated 4 times. Then, the dried boron fiber was placed in a tubular furnace, and heated to 940°C at a heating rate of 9°C / min in a nitrogen atmosphere, and kept warm for 115 minutes. After completion, the reaction mixture was cooled to room temperature at a cooling rate of 7°C / min under a nitrogen atmosphere to obtain reinforced fibers.

[0067] Furthermore, the composite material is compounded by phenolic resin and furfural in a mass ratio of 1:2.4.

[0068] In this embodiment, it should be noted that the phenolic resin was purchased from Jinan Dahui Chemical Technology Co., Ltd., the furfural was purchased from Shandong Qiyun Chemical Technology Co., Ltd., and the boron fiber was purchased from Hubei Langbowan Biomedicine Co., Ltd.

[0069] In addition, the method for improving the tensile strength of the metal connector material provided in this embodiment includes the following steps: Step 1: Accurately weigh titanium powder, aluminum powder, niobium powder, chromium powder, cobalt powder, high entropy alloy powder and reinforcing fiber, and put the titanium powder, aluminum powder, niobium powder, chromium powder, cobalt powder, high entropy alloy powder and reinforcing fiber into a mixing equipment for mixing.

[0070] Step 2: After the mixture is evenly mixed, the mixture is pressed into a green compact to obtain a green compact.

[0071] The pressure applied in the compacting process is 128 kN, and the holding time is 14 s.

[0072] Step 3: ignite the obtained billet by laser in an argon atmosphere to obtain an alloy billet.

[0073] Among them, the laser power used for laser ignition is 1700W, the spot diameter is 21mm, and the irradiation time is 19s.

[0074] Step 4: subjecting the obtained alloy billet to vacuum induction melting, and inserting an ultrasonic probe into the alloy liquid for ultrasonic treatment.

[0075] Among them, the process of vacuum induction melting is as follows: The first stage: power is 20KW, time is 11 minutes; The second stage: power is 40KW, time is 11 minutes; The third stage: the power is 80KW, until the alloy is completely melted; The fourth stage: power is 100KW, time is 28min; The vacuum degree of vacuum induction melting is 1.6Pa.

[0076] The power of ultrasonic treatment was 1400 W, the frequency of ultrasonic treatment was 21 KHz, and the time was 5 s.

[0077] Step 5: Then pour the alloy liquid, and after cooling, obtain the finished metal connector material. Example 5

[0078] The present embodiment provides a method for improving the tensile strength of a metal connector material, wherein the metal connector material is composed of the following raw materials in parts by weight: 12 parts of titanium powder, 15 parts of aluminum powder, 10 parts of niobium powder, 8 parts of chromium powder, 7 parts of cobalt powder, 10 parts of high entropy alloy powder and 8 parts of reinforcing fiber.

[0079] Among them, the preparation process of high entropy alloy powder is as follows: Accurately weigh iron powder, nickel powder, manganese powder, tantalum powder and yttrium powder and set aside; The iron powder, nickel powder, manganese powder, tantalum powder and yttrium powder are placed in a planetary ball mill, stearic acid is added thereto, and ball milling is performed under an argon atmosphere to obtain a high entropy alloy powder; Furthermore, the added amount mass ratio of iron powder, nickel powder, manganese powder, tantalum powder and yttrium powder is 1:1.12:1.25:0.95:0.82; The added amount of stearic acid is 0.3% of the total mass of iron powder, nickel powder, manganese powder, tantalum powder and yttrium powder.

[0080] In addition, the ball-to-material ratio of the ball mill is 7.5:1, the rotation speed of the ball mill is 160 r / min, and the ball milling time is 120 min.

[0081] The preparation process of the reinforcing fiber is as follows: The composite material was placed in ethanol at a mass ratio of 0.3:1, heated to 50°C at 400 r / min, and then stirred for 100 min to obtain a pre-prepared solution; The boron fiber was completely immersed in the pre-prepared solution for 30 minutes, taken out, and naturally dried at room temperature, and then immersed for 4 times. Then, the dried boron fiber was placed in a tubular furnace, and heated to 950°C at a heating rate of 10°C / min under a nitrogen atmosphere, and kept warm for 120 minutes; After completion, the reaction mixture was cooled to room temperature at a cooling rate of 8°C / min under a nitrogen atmosphere to obtain reinforced fibers.

[0082] Furthermore, the composite material is compounded by phenolic resin and furfural in a mass ratio of 1:2.5.

[0083] In this embodiment, it should be noted that the phenolic resin was purchased from Jinan Dahui Chemical Technology Co., Ltd., the furfural was purchased from Shandong Qiyun Chemical Technology Co., Ltd., and the boron fiber was purchased from Hubei Langbowan Biomedicine Co., Ltd.

[0084] In addition, the method for improving the tensile strength of the metal connector material provided in this embodiment includes the following steps: Step 1: Accurately weigh titanium powder, aluminum powder, niobium powder, chromium powder, cobalt powder, high entropy alloy powder and reinforcing fiber, and put the titanium powder, aluminum powder, niobium powder, chromium powder, cobalt powder, high entropy alloy powder and reinforcing fiber into a mixing equipment for mixing.

[0085] Step 2: After the mixture is evenly mixed, the mixture is pressed into a green compact to obtain a green compact.

[0086] The pressure applied in the compacting process is 130 kN, and the holding time is 15 s.

[0087] Step 3: ignite the obtained billet by laser in an argon atmosphere to obtain an alloy billet.

[0088] Among them, the laser power used for laser ignition is 1800W, the spot diameter is 22mm, and the irradiation time is 20s.

[0089] Step 4: subjecting the obtained alloy billet to vacuum induction melting, and inserting an ultrasonic probe into the alloy liquid for ultrasonic treatment.

[0090] Among them, the process of vacuum induction melting is as follows: The first stage: power is 20KW, time is 12min; The second stage: power is 40KW, time is 12min; The third stage: the power is 80KW, until the alloy is completely melted; The fourth stage: power is 100KW, time is 30min; The vacuum degree of vacuum induction melting is 1.8Pa.

[0091] The power of ultrasonic treatment was 1500 W, the frequency of ultrasonic treatment was 22 KHz, and the time was 6 s.

[0092] Step 5: Then pour the alloy liquid, and after cooling, obtain the finished metal connector material. Comparative Example 1

[0093] The difference from Example 1 is that this example does not contain high entropy alloy powder. Comparative Example 2

[0094] The difference from Example 1 is that the high entropy alloy powder in this embodiment does not contain tantalum powder. Comparative Example 3

[0095] The difference from Example 1 is that in this example, an equal amount of boron fibers are used instead of reinforcing fibers. Comparative Example 4

[0096] The difference from Example 1 is that the vacuum induction melting in this example does not include the fourth stage. Comparative Example 5

[0097] The difference from Example 1 is that in this embodiment, no ultrasonic probe is inserted for ultrasonic treatment.

[0098] The metal connector material samples provided in Examples 1 to 5 and Comparative Examples 1 to 5 are marked as Examples 1 to 5 and Comparative Examples 1 to 5, respectively; and the relevant properties of the metal connector materials provided in Examples 1 to 5 and Comparative Examples 1 to 5 are tested as follows: 1. Mechanical test: The test method is to use a WDW-50 electronic universal testing machine to test the tensile strength and elongation. 2. Vibration fatigue test: The test method is to test the initial elastic modulus of each group of samples, and stretch them on a ZDM-2.5T / 91 material testing machine with a 415 mirror extensometer to obtain the initial elastic modulus of each sample; then take each group of samples for fatigue vibration test in accordance with GB / T3075-82 "Metal Axial Fatigue Test Method", using a DL-10 vibration fatigue testing machine to vibrate 200,000 times at 80Mpa, the vibration mode is rotary, the amplitude is 25.4mm, and the vibration frequency is 300rpm. After completing the vibration test, the elastic modulus is measured in the same way as above to obtain the terminal elastic modulus of each sample; finally, the elastic modulus loss rate (%) = (initial elastic modulus - terminal elastic modulus) / initial elastic modulus is calculated.

[0099] The obtained test data are recorded in Table 1 and Table 2 below:

[0100] Table 1 Mechanical properties test results of each group of metal connector materials

[0101] Table 2 Test results of vibration fatigue resistance of metal connector materials in each group

[0102] By comparing and analyzing the relevant data in Table 1 and Table 2, it can be seen that the method for improving the tensile strength of the metal connector material provided by the present invention can not only effectively improve the mechanical properties of the prepared metal connector material, but also improve the anti-vibration fatigue performance, effectively ensuring its quality. This shows that the method for improving the tensile strength of the metal connector material provided by the present invention has a broader market prospect and is more suitable for promotion.

[0103] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0104] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for improving the tensile strength of a metal connector material, characterized in that: The metal connector material is composed of the following raw materials in parts by weight: 8 to 12 parts of titanium powder, 10 to 15 parts of aluminum powder, 5 to 10 parts of niobium powder, 5 to 8 parts of chromium powder, 4 to 7 parts of cobalt powder, 6 to 10 parts of high entropy alloy powder and 4 to 8 parts of reinforcing fiber; The method for improving the tensile strength of the metal connecting piece material comprises the following steps: Step 1: Accurately weigh titanium powder, aluminum powder, niobium powder, chromium powder, cobalt powder, high entropy alloy powder and reinforcing fiber, and put the titanium powder, aluminum powder, niobium powder, chromium powder, cobalt powder, high entropy alloy powder and reinforcing fiber into a mixing equipment for mixing; Step 2: After the mixture is evenly mixed, the mixture is pressed into a green compact to obtain a green compact; Step 3, igniting the obtained billet by laser in an argon atmosphere to obtain an alloy billet; Step 4: subjecting the obtained alloy billet to vacuum induction melting, and inserting an ultrasonic probe into the alloy liquid for ultrasonic treatment; Step 5: Then pour the alloy liquid, and after cooling, obtain the finished metal connector material.

2. A method for improving the tensile strength of a metal connector material according to claim 1, characterized in that: The preparation process of the high entropy alloy powder is as follows: Accurately weigh iron powder, nickel powder, manganese powder, tantalum powder and yttrium powder and set aside; The iron powder, nickel powder, manganese powder, tantalum powder and yttrium powder are placed in a planetary ball mill, stearic acid is added thereto, and ball milling is performed under an argon atmosphere to obtain a high entropy alloy powder; The added amount mass ratio of the iron powder, nickel powder, manganese powder, tantalum powder and yttrium powder is 1:1.05-1.12:1.14-1.25:0.85-0.95:0.68-0.82; The added amount of the stearic acid is 0.2-0.3% of the total mass of the iron powder, nickel powder, manganese powder, tantalum powder and yttrium powder.

3. A method for improving the tensile strength of a metal connector material according to claim 2, characterized in that: The ball-to-material ratio of the ball mill is 7.2-7.5:1, the rotation speed of the ball mill is 150-160 r / min, and the ball milling time is 100-120 min.

4. A method for improving the tensile strength of a metal connector material according to claim 1, characterized in that: The preparation process of the reinforcing fiber is as follows: The composite material is placed in ethanol at a mass ratio of 0.2 to 0.3:1, heated to 40 to 50°C at 200 to 400 r / min, and then stirred for 60 to 100 minutes to obtain a pre-formulated solution; The boron fiber is completely immersed in the pre-prepared solution for 20 to 30 minutes, taken out, and naturally dried at room temperature, and then the immersed state is repeated 3 to 4 times, and then the dried boron fiber is placed in a tubular furnace, and the temperature is increased to 850 to 950°C at a heating rate of 5 to 10°C / min under a nitrogen atmosphere, and the temperature is kept for 90 to 120 minutes; After completion, the reaction mixture was cooled to room temperature at a cooling rate of 3 to 8°C / min under a nitrogen atmosphere to obtain reinforced fibers.

5. A method for improving the tensile strength of a metal connector material according to claim 4, characterized in that: The composite material is prepared by mixing phenolic resin and furfural in a mass ratio of 1:2.2-2.

5.

6. A method for improving the tensile strength of a metal connector material according to claim 1, characterized in that: The pressure applied in the green compaction process is 120-130 kN, and the holding time is 10-15 s.

7. A method for improving the tensile strength of a metal connector material according to claim 1, characterized in that: The laser ignition adopts a laser power of 1500-1800W, a spot diameter of 18-22mm, and an irradiation time of 12-20s.

8. The method for improving the tensile strength of a metal connector material according to claim 1, characterized in that: The process of vacuum induction melting is as follows: The first stage: power is 20KW, time is 10-12 minutes; The second stage: power is 40KW, time is 10-12 minutes; The third stage: the power is 80KW, until the alloy is completely melted; The fourth stage: the power is 100KW and the time is 20 to 30 minutes.

9. A method for improving the tensile strength of a metal connector material according to claim 1, characterized in that: The vacuum degree of the vacuum induction melting is less than 2Pa.

10. A method for improving the tensile strength of a metal connector material according to claim 1, characterized in that: The power of the ultrasonic treatment is 1200-1500W, the ultrasonic frequency is 20-22KHz, and the time is 4-6s.

Citation Information

Patent Citations

  • Ultrafine carbide particle reinforced metal-based composite material and preparation method thereof

    CN109852830A

  • Aluminum-niobium-tantalum intermediate alloy and preparation method thereof

    CN116397138A

  • Efficient-grinding boron-containing high-entropy alloy and diamond combined superhard composite material and preparation method and application thereof

    CN116574954A

  • Method for preparing refractory high-entropy alloy through electron beam smelting and remelting return scraps

    CN116790924A

  • Snow melting system

    KR102280829B1